Analysis of The EwacsPro Auto Dispatch System in XYZ Company Using Technology Readiness Level (TRL) and Technology Acceptance Model 2 (TAM2) Adoption - Risoyo, Imam Andrian; Taufik, Tatang Akhmad (Institut Teknologi dan Bisnis Bina Sarana Global, 2024)
Fleet Management System (FMS) is a system that quite good to manage the haul cycle and can be useful for reducing the idle time of the conveyance. The development of an FMS with an Auto Dispatch System (ADS) that utilizes digital information technology can make management easier. ADS is the system which has assignment logic systems for transport equipment, either directly suggesting to the operator through computerized systems or through dispatchers. XYZ Company developed its own ADS, called Early Warning & Control System Pro (EwacsPro), which has been tested on 1 of 4 total pits they have in ABC jobsite, using the LTE Communication network, which is the first in Indonesia. The problem behind this research is that the system has never been tested for readiness. This research aims to analyze, evaluate and explore the level of readiness of the EwacsPro system using the Technology Readiness Level (TRL) method and also analyze the level of operator acceptance of the use of the EwacsPro system adopting Technology Accetance Model 2 (TAM2) using Structural Equation Modeling (SEM) analysis. The research will provide recommendations to the XYZ management for improvements related to EwacsPro at ABC Jobsite so that it can provide benefits according to the technological design which has been made, using Business Model Canvas (BMC) tool. The EwacsPro system reached level 9 TRL with a fulfillment rate of 80%. There are 7 variables that significantly influence EwacsPro's Usage Behavior directly and 1 variable that significantly influences using 2 influencing moderator variables of the TAM2 analysis. The R-square test also shows that all values are above 0.75, which means that there is a strong influence from the measurement of the exogenous latent variable on the endogenous latent variable.